Sevoflurane promotes premature differentiation of dopaminergic neurons in hiPSC-derived midbrain organoids - Shang, Jia; Li, Bin; Fan, Han; Liu, Peidi; Zhao, Wen; Chen, Tao; Chen, Pu; Yang, Longqiu (Frontiers in Cell and Developmental Biology, 2022)
Background: Conventional animal models used in corresponding basic studies are distinct from humans in terms of the brain’s development trajectory, tissue cytoarchitecture and cell types, making it difficult to accurately evaluate the potential adverse effects of anesthetic treatments on human fetal brain development. This study investigated the effects of sevoflurane on the midbrain’s development and cytopathology using human physiologically-relevant midbrain organoids. Methods: Monolayer human induced pluripotent stem cells (hiPSC)-derived human floor plate cells and three-dimensional hiPSC-derived midbrain organoids (hMBOs) were exposed to 2% (v/v) sevoflurane for 2 or 6 h, followed by expansion or differentiation culture. Then, immunofluorescence, real-time PCR, EdU assay, Tunnel assay, and transcriptome sequencing were performed to examine the effects of sevoflurane on the midbrain’s development. Results: We found that 2% sevoflurane exposure inhibited hFPCs’ proliferation (differentiation culture: 7.2% ± 0.3% VS. 13.3% ± 0.7%, p = 0.0043; expansion culture: 48% ± 2.2% VS. 35.2% ± 1.4%, p = 0.0002) and increased their apoptosis, but did not affect their differentiation into human dopaminergic neurons After 6 h, 2% sevoflurane exposure inhibited cell proliferation (62.8% ± 5.6% VS. 100% ± 5.5%, p = 0.0065) and enhanced the premature differentiation of hMBOs (246% ± 5.2% VS. 100% ± 28%, p = 0.0065). The RNA-seq results showed long-term exposure to sevoflurane up regulates some transcription factors in the differentiation of dopaminergic neurons, while short-term exposure to sevoflurane has a weak up-regulation effect on these transcription factors. Conclusion: This study revealed that long-term exposure to sevoflurane could promote the premature differentiation of hMBOs, while short-term exposure had negligible effects, suggesting that long-term exposure to sevoflurane in pregnant women may lead to fetals’ midbrain development disorder.